Gut microbiota: emerging biomarkers and potential therapeutics for premature ovarian failure - Liu, Zongyu; Wang, Min; Lei, Yuanyuan; Xu, Kaiqi; Fan, Limei (Frontiers in Microbiology, 2025)
Premature ovarian failure is a prevalent gynecological endocrine disorder with an increasing incidence rate each year, impacting women’s physical and mental health. The causes of POF are poorly understood, but genetic, immune, iatrogenic, environmental, and psychological factors are key contributors. Clinically, POF manifests as oligomenorrhea, amenorrhea, elevated follicle-stimulating hormone (FSH) levels, and decreased estrogen levels, leading to infertility in women. POF not only impacts reproductive function but also elevates the risk of cardiovascular diseases, osteoporosis, depression, anxiety, cognitive decline, and neurological disorders, thereby adversely affecting women’s mental health and quality of life over the long term. The gut microbiota (GM) comprises a vast and complex microbial community within the human gastrointestinal tract. GM dysregulation is closely associated with numerous human diseases, including autoimmune diseases, allergic disorders, cardiovascular diseases, cancers, and metabolic disorders. Studies have shown that GMs play a pivotal role in female reproductive health, participating in the pathogenesis of reproductive endocrine disorders through direct or indirect involvement in sex hormone regulation, stimulation of inflammatory cytokine production, modulation of immune function, metabolic homeostasis, and regulation of neurotransmitter synthesis. Recently, advancements in human microbiology have highlighted the significant interest in the connection between POF and the gut microbiome. Researching the molecular mechanisms by which GMs and their metabolites regulate the occurrence of POF opens up a new direction for studying the pathogenesis of POF. This research aims to identify an efficient, non-invasive, and accurate diagnostic method for clinical diagnosis and treatment of POF, providing novel theoretical insights and precise intervention strategies for the clinical prevention and treatment of POF.